Induction chemotherapy integrated treatment programs for locally advanced cancers - Aigner, K. (Karl) 1947-; Stephens, Fred. (Heidelberg, Germany Springer Berlin, 2011)
Induction chemotherapy, as part of an integrated plan of management for locally advanced cancers, is being practised throughout the world in independent, isolated departments in universities, teaching hospitals, and clinical schools. Frequently, however, teams are relatively unaware of the work being undertaken in other institutions, and this situation may slow further progress. This book aims to present the full range of management techniques and practices used in induction chemotherapy within one accessible volume. It provides up-to-date information on the pioneering and cutting edge practices employed in different institutions and documents the advantages of integrated treatment schedules. Patient selection is discussed, and each of the cancer types for which induction therapy has proved important is considered in detail. All who are responsible for the treatment of patients with locally advanced cancers will find this book to be an invaluable source of information. It will be particularly interesting for specialist oncologists aiming to set up and develop fully comprehensive cancer centres and for health administrators wishing to learn about the benefits of establishing such centres in strategic locations.
Introduction: Overview, History, Terminology and Early Clinical Experience -- The Principle of Dose-Response in Antineoplastic Drug Delivery -- Drug Removal Systems and Induction Chemotherapy -- Cryotherapy -- Local and Regional Hyperthermia -- The Role of Hypoxia and Hyperthermia in Chemotherapy -- Induction Chemotherapy in Head and Neck Cancers -- Isolated Thoracic Perfusion with Carotid Artery Infusion for Advanced and Chemoresistant Tumors of the Parotid Gland -- Induction Systemic Chemotherapy for Breast Cancer -- Induction Intra-arterial Chemotherapy (IAC) with Epirubicin and Mitoxantrone in Locally Advanced Breast Cancer -- Induction Bidirectional Chemotherapy for Gastric Cancer with Peritoneal Dissemination -- Gastric Cancer -- Esophageal Cancer -- Regional Chemotherapy for Recurrent Platin Refractory Ovarian Cancer -- Penile Cancer Treated by Intra-aortic Infusion Chemotherapy -- Isolated Limb Perfusion for Melanoma -- Interventional Radiological Procedures for Port-Catheter Implantation -- Induction Chemotherapy for Hepatocellular Carcinoma -- Systemic Induction Chemotherapy for Advanced Stage Epithelial Ovarian Cancer -- Induction Chemotherapy for Cervical Cancer -- Induction Treatment in Sarcomas -- Induction Chemotherapy in Treatment of Sarcomas -- Liver Metastases -- Isolated Thoracic Perfusion with Chemofiltration (ITP-F) for Advanced and Pre-treated Non-Small-Cell Lung Cancer -- Isolation Perfusion Systems: Lungs -- Metastatic Cancers in Lung: Isolated Lung Perfusion -- Clinical Studies -- Systemic and Regional Chemotherapy for Advanced and Metastasized Pancreatic Cancer -- Conclusion.
Electronic reproduction.
Keywords: Chemotherapy